In vitro biodegradation of three brushite calcium phosphate cements by a macrophage cell-line. - Xia, Z; Grover, L; Huang, Y; Adamopoulos, I; Gbureck, U; Triffitt, J; Shelton, R; Barralet, J (2006)
Depending upon local conditions, brushite (CaHPO4 x 2 H2O) cements may be largely resorbed or (following hydrolysis to hydroxyapatite) remain stable in vivo. To determine which factors influence cement resorption, previous studies have investigated the solution-driven degradation of brushite cements in vitro in the absence of any cells. However, the mechanism of cell-mediated biodegradation of the brushite cement is still unknown. The aim of the current study was to observe the cell-mediated biodegradation of brushite cement formulations in vitro. The cements were aged in the presence of a murine cell line (RAW264.7), which had the potential to form osteoclasts in the presence of the receptor for nuclear factor kappa B ligand (RANKL) in vitro, independently of macrophage colony stimulating factor (M-CSF). The cytotoxicity of the cements on RAW264.7 cells and the calcium and phosphate released from materials to the culture media were analysed. Scanning electron microscopy (SEM) and focused ion beam (FIB) microscopy were used to characterise the ultrastructure of the cells. The results showed that the RAW264.7 cell line formed multinucleated TRAP positive osteoclast-like cells, capable of ruffled border formation and lacunar resorption on the brushite calcium phosphate cement in vitro. In the osteoclast-like cell cultures, ultrastructural analysis by SEM revealed phenotypic characteristics of osteoclasts including formation of a sealing zone and ruffled border. Penetration of the surface of the cement, was demonstrated using FIB, and this showed the potential demineralising effect of the cells on the cements. This study has set up a useful model to investigate the cell-mediated cement degradation in vitro.